1984
DOI: 10.3354/meps020165
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in selected body tissues of the scallop Patinopecten yessoensis under long-term exposure to low Cd concentrations

Abstract: Effects of low cadmium concentrations (0.5 pg Cd 1 ' ) on uptake, alkaline phosphatase activity and zinc content of scallops Patinopecten yessoensis were investigated during 25 d exposure. Cadmium accumulations in digestive gland were bound to cytoplasmic intermediate molecular weight proteins. No adverse damage was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Nuclei, mitochondria, microsomes and cytosol were separated using a widely accepted method (Fleisher and Kervina 1974). Cytoplasmic proteins were isolated from hepatopancreas, gills and kidney as previously described (Evtushenko et al 1984). Cytoplasmic proteins were isolated from hepatopancreas, gills and kidney as previously described (Evtushenko et al 1984).…”
Section: Methodsmentioning
confidence: 75%
“…Nuclei, mitochondria, microsomes and cytosol were separated using a widely accepted method (Fleisher and Kervina 1974). Cytoplasmic proteins were isolated from hepatopancreas, gills and kidney as previously described (Evtushenko et al 1984). Cytoplasmic proteins were isolated from hepatopancreas, gills and kidney as previously described (Evtushenko et al 1984).…”
Section: Methodsmentioning
confidence: 75%
“…Kidney is considered one of the most important organs in detoxification and elimination of trace metals in the Pectinidae family, proteins such as metallothionein are involved in Cd detoxification and later elimination through excretion from this organ (George et al, 1980 cited by Bustamante andMiramand, 2004). Pecten species such as P. yessoensis, A. colbecki, Chlamys varia, Aequipecten operculis and P. maximus reduced and detoxified considerably metal burdens in different tissues after processes of depuration or dilution (by growth) of metals either in field or laboratory conditions (Evtushenko et al, 1984;Viarengo et al, 1993;Bustamante and Miramand, 2004). In our study, a two-fold reduction of Cd and Pb levels was observed in gonad of PN6 and PN3 when comparing the 2nd and 3rd month with those at the 4th month (see Table 1), this may be influenced by detoxification mechanisms, as well as organism's physiological adaptations such as a shift to low metabolic rates and closure of their shells to avoid the uptake of contaminants (Neff, 2002).…”
Section: And Pb Levels Throughout the Experimentsmentioning
confidence: 98%
“…The evaluation considered individuals that were 6-11 years old, whose Cd concentrations (lg/g dry weight) varied from 130 ± 25 in August and 54.1 ± 9.0 in November (1998), to 86 ± 22 in January, 73.2 ± 24 in March and 167 ± 75 in June (1999) (Bel'cheva et al, 2002). Patinopecten yessoensis individuals exposed to low Cd concentrations also showed high variations with no apparent trend in gonad and muscle levels (lg/g dry matter), about 3.4 (0-d), 4.8 (7-d), 16.5 (15-d), 9.6 (20-d) an 14.0 (25-d) in gonad and 1.5 (0-d), 1.0 (7-d), 1.1 (15-d), 1.9 (20-d) and 2.0 (25-d) in muscle during 25 days of experimentation (Evtushenko et al, 1984). Several studies demonstrated that pecten species are able to accumulate high amounts of trace metals but till certain point, then different mechanisms of elimination are usually performed in order to reduce the internalized metal (Viarengo et al, 1993).…”
Section: And Pb Levels Throughout the Experimentsmentioning
confidence: 99%
“…Only after 60 days had the metal begun penetrating low molecular weight metallothionein-like proteins. The same species was exposed at length to 0.5 f.Lg Cd I-I (Evtushenko et at., 1984). In this case, Cd was present only in MT-like proteins and was not bound to HMWP.…”
Section: Interactions Within the Cellmentioning
confidence: 99%